2006
DOI: 10.1248/bpb.29.397
|View full text |Cite
|
Sign up to set email alerts
|

Safe and Efficient Drug Delivery System with Liposomes for Intrathecal Application of an Antivasospastic Drug, Fasudil

Abstract: Pharmacological treatment for cerebral ischemia and cerebral vasospasm following subarachnoid hemorrhage (SAH) cannot attain sufficiently high concentrations of the drugs in the cerebrospinal fluid (CSF) without precipitating systemic side effects. We recently developed a liposomal drug delivery system for intrathecal application that can maintain effective concentrations of cerebral vasodilator, fasudil, in the CSF. A single intrathecal injection of liposomal fasudil could maintain a therapeutic drug concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 48 publications
(46 reference statements)
0
14
0
1
Order By: Relevance
“…It is reported that relatively higher doses of fasudil (14 -48 mg⅐kg Ϫ1 ⅐day Ϫ1 ) produce a blocking action against calcium entry (2, 23) as well as an inhibitory effect on protein kinase C (3,23). We did not examine the intracellular calcium levels or protein kinase C levels in this study.…”
Section: Discussionmentioning
confidence: 94%
“…It is reported that relatively higher doses of fasudil (14 -48 mg⅐kg Ϫ1 ⅐day Ϫ1 ) produce a blocking action against calcium entry (2, 23) as well as an inhibitory effect on protein kinase C (3,23). We did not examine the intracellular calcium levels or protein kinase C levels in this study.…”
Section: Discussionmentioning
confidence: 94%
“…Preliminary experiments revealed that the half-life of HA-1077 injected directly into the eye was less than 24 hrs (data not shown), indicating that a more sustained release would be necessary. To improve the bioavailability of HA-1077, we packaged it into liposomes using palmitoyloleoylphosphatidylcholine (POPC) and cholesterol with remote loading approaches [24], [25], [26]. This method of drug delivery has been shown to provide sustained release within the intra-ocular space over several weeks [25], [26], [27].…”
Section: Resultsmentioning
confidence: 99%
“…Liposomes are biocompatible and biodegradable drug carriers that have the potential to enhance the potency and reduce the toxicity of therapeutic agents (Lian & Ho 2001). However, conventional liposomes do not undergo significant transport through the BBB in the absence of vector-mediated drug delivery (Misra et al 2003;Ishida et al 2006). Furthermore, these liposomes are coated with serum proteins immediately after intravenous administration and are rapidly removed from the bloodstream and cleared by the cells of the reticuloendothelial system (RES; Siwak et al 2002;Sadzuka et al 2006).…”
Section: Systemic Drug Delivery Systemsmentioning
confidence: 99%